Evolution, diversification, and expression of KNOX proteins in plants - Gao, Jie; Yang, Xue; Zhao, Wei; Lang, Tiange; Samuelsson, Tore (Frontiers in Plant Science, 2015)
The KNOX (KNOTTED1-like homeobox) transcription factors play a pivotal role in leaf and meristem development. The majority of these proteins are characterized by the KNOX1, KNOX2, ELK and homeobox domains whereas the proteins of the KNATM family contain only the KNOX domains. We carried out an extensive inventory of these proteins and here report on a total of 394 KNOX proteins from 48 species. The land plant proteins fall into two classes (I and II) as previously shown where the class I family seems to be most closely related to the green algae homologs. The KNATM proteins are restricted to Eudicots and some species have multiple paralogs of this protein. Certain plants are characterized by a significant increase in the number of KNOX paralogs; one example is Glycine max. Through the analysis of public gene expression data we show that the class II proteins of this plant have a relatively broad expression specificity as compared to class I proteins, consistent with previous studies of other plants. In G. max, class I protein are mainly distributed in axis tissues and KNATM paralogs are overall poorly expressed; highest expression is in the early plumular axis. Overall, analysis of gene expression in G. max demonstrates clearly that the expansion in gene number is associated with functional diversification.